Development of a New Module of the FACE-Q for Children and Young Adults with Diverse Conditions Associated with Visible and/or Functional Facial Differences - Longmire, Natasha M.; Wong Riff, Karen W.Y.; O'Hara, Justine L.; Aggarwala, Shivani; Allen, Gregory C.; Bulstrode, Neil W.; Forrest, Christopher R.; French, Brooke M.; Goodacre, Timothy E.E.; Marucci, Damian; Norris, Jonathan H.; Panchapakesan, Vivek; Piplani, Bhoomika; Pusic, Andrea L.; Vercruysse, Herman Jr.; Klassen, Anne F. (Facial Plastic Surgery, 2017)
Appearance and facial function are concepts not well addressed in current pediatric patient-reported outcome measures (PROM) for facial conditions. We aimed to develop a new module of the FACE-Q for children/young adults with facial conditions that include ear anomalies, facial paralysis, skeletal conditions, and soft tissue conditions. Semi-structured and cognitive interviews were conducted with patients aged 8–29 years recruited from craniofacial centers in Canada, USA, UK, and Australia. Interviews were used to elicit new concepts and to obtain feedback on CLEFT-Q scales hypothesized to be relevant to other facial conditions. Interview data were recorded, transcribed, and coded. Experts were emailed and invited to provide feedback via Research Electronic Data Capture (REDCap). Eighty-four participants and 43 experts contributed. Analysis led to the development of a conceptual framework and 14 new scales that measure appearance, facial function, health-related quality of life, and adverse effects of treatment. In addition, 12 CLEFT-Q scales were determined to have content validity for use with other facial conditions. Expert input led to minor changes to scales and items. This new FACE-Q module for children/young adults is being field-tested internationally. Once finalized, we anticipate this PROM will be used to inform clinical practice and research studies.
Keywords: facial differences; quality of life; patient-reported outcome measure; FACE-Q